Application of used engine oil in the asphalt pavement industry. Issue 1 (1st February 2022) - Raţiu, S; Benea, L; Armioni, M
Abstract: The automotive industry presents a number of significant problems at the moment, including the waste it produces. Used engine oil is an eloquent example in this regard, as significant amounts of spent lubricant are generated annually, with a high pollutant potential. If conventional recycling measures cannot be applied, it is necessary to find alternative management solutions that do not allow the used oil to reach the environment. This article aims to present a review of the recovery of used engine oil in the asphalt pavement production and rejuvenation industry, as well as to emphasize the improvements brought by the used engine oil on the reclaimed asphalt pavement.